Profitable failure: antidepressant drugs and the triumph of flawed experiments - McGoey, L (SAGE Publications, 2010)
Drawing on an analysis of Irving Kirsch and colleagues’ controversial 2008 article in PLoS [Public Library of Science] Medicine on the efficacy of SSRI antidepressant drugs such as Prozac, I examine flaws within the methodologies of randomized controlled trials (RCTs) that have made it difficult for regulators, clinicians and patients to determine the therapeutic value of this class of drug. I then argue, drawing analogies to work by Pierre Bourdieu and Michael Power, that it is the very limitations of RCTs — their inadequacies in producing reliable evidence of clinical effects — that help to strengthen assumptions of their superiority as methodological tools. Finally, I suggest that the case of RCTs helps to explore the question of why failure is often useful in consolidating the authority of those who have presided over that failure, and why systems widely recognized to be ineffective tend to assume greater authority at the very moment when people speak of their malfunction.